دور حوكمت الموارد الطاقية في تحقيق التنمية المستدامة للاقتصاد الجزائري - جغبالة، عبد الغني (University Of Eloued جامعة الوادي, 2025)
تهدف الدراسة إلى البحث حول تاثير تطبيق حوكمة الموارد الطاقوية في تحقيق التنمية المستدامة للإقتصاد الجزائري، لمجموعة من فروع المؤسسة الوطنية سوناطراك، من خلال التوجه نحو الاستغلال الأمثل للموارد الطاقوية التقليدية، لدعم سياسة طاقوية تشجع على استخدام الطاقات المتجددة، وتطوير التكنولوجيات النظيفة التي بدورهاتحقق التنمية المستدامة ، تم الاعتماد على المنهج الوصفي التحليلي من خلال الاستبانة والمقابلة وجمع البيانات لعينة دراسة التي تمثلث في 228 من العاملين مؤسسة سونطراك، حيث تم الاعتماد علىى تحليل البيانات ومعالجتها باستخدام البرنامج الإحصائي SPSSV25 النسخة 25، إضافة إلى برنامج AMOS ،وتوصلت الدراسة إلى النتائج التالية: • ينعكس تطبيق الشفافية والمساءلة لحوكمة الموارد الطاقوية إيجابا في تحقيق أبعاد التنمية المستدامة بالمؤسسات محل الدراسة. • ينعكس تطبيق الشفافية والمساءلة لحوكمة الموارد الطاقوية إيجابا في تحقيق أبعاد التنمية المستدامة في المؤسسات محل الدراسة. • ينعكس تطبيق إشراك أصحاب المصلحة لحوكمة الموارد الطاقوية إيجابا في تحقيق أبعاد التنمية المستدامة في المؤسسات محل الدراسة. • توجد فروق ذات دلالة إحصائية لوجهات نظر المستجوبين حول توفر أبعاد متغيرات الدراسة في المؤسسات محل الدراسة تعزى للعوامل الديمغرافية (العمر، المؤهل العلمي، المسمى الوظيفي، الخبرة المهنية، ....). Abstract: The study seeks to examine the effects of energy resource governance implementation on attaining sustainable development within the Algerian economy, specifically among many subsidiaries of Sonatrach. This accomplished by prioritizing the efficient utilization of conventional energy resources, endorsing an energy policy that promotes renewable energy adoption and the advancement of clean technology, hence facilitating sustainable development. The research employed a descriptive analytical methodology including questionnaires, interviews, and data collection from a sample of 228 Sonatrach personnel. Data evaluated and processed utilizing the statistical software SPSS V25, version 25, with the AMOS program. The research yielded the subsequent findings: • The implementation of transparency and accountability in energy resource governance positively influences the attainment of sustainable development features within the examined institutions. • The implementation of transparency and accountability in energy resource governance positively influences the attainment of sustainable development features within the examined institutions. • The implementation of stakeholder involvement in energy resource governance positively influences the attainment of sustainable development features within the examined institutions. • Statistically significant disparities exist in respondents' perceptions of the availability of study variables within the institutions examined, attributable to demographic factors such as age, educational qualifications, job title, and professional experience.
Thesis
Keywords: حوكمة; موارد; طاقة; تنمية; مستدامة; سونا طراك; Governance; resources; energy; development; sustainable; sonatrach